Edge of awareness 25 contemporary essays - Hoopes, Ned E.; Peck, Richard 1934- (Laurel-leaf library, 1966)
Contains essays in five catagories: Defining oneself and others; Searching for meaning in a complex society; Attaining a unique place; Responding to creative experiences; Surviving through science.